Experimental study on classical and metaheuristics algorithms for optimal nano-chitosan concentration selection in surface coating and food packaging. (15th January 2021) - Dadvar, Ali Akbar; Vahidi, Javad; Hajizadeh, Zoleikha; Maleki, Ali; Reza Bayati, Mohammad
Graphical abstract: Highlights: Algorithm solved the problem of hydrophobic functional food packaging fabrication. Neither additional chemicals nor extra initial test were used in the present work. POA, WOA and GOA were applied and compared to find the optimal chitosan NPs. It can be applied for the previous optimization studies as well as the future ones. POA optimizes experimental replicate models, represented apple nano coating. Abstract: In this study the Lagrange interpolation optimization algorithm based on two variables with respect to all experimental replicates (POA), was compared with two other heuristics methods (WOA and GOA). Modification of the apple surface by an edible nano coating solution in food packaging was used as case study. The experiment was performed as a factorial test based on completely randomized design by 100 permutations data sets. Results showed a significant difference between the three optimization methods (POA, WOA and GOA) which indicates the necessity of optimization and also efficiency of the present POA. The optimum result by POA, similar to a rose petal property, could rise 72% in surface contact angle (CA). The scanning electron microscopy (SEM) images of the derived surfaces showed almost a uniform spherical nanoparticles morphology. Remarkable advantages of this new approach are no additional material requirement, healthful, easy, inexpensive, fast and affordable technique for surface improvement.